2005
DOI: 10.1530/eje.1.01933
|View full text |Cite
|
Sign up to set email alerts
|

Hip bone mineral density, bone turnover and risk of fracture in patients on long-term suppressive L-thyroxine therapy for differentiated thyroid carcinoma

Abstract: Objective: Untreated hyperthyroidism and treatment with high doses of thyroid hormone are associated with osteoporosis. However, their effect on bone turnover, their contribution to bone mineral density (BMD) in the context of other clinical risk factors for osteoporosis and the prevalence of vertebral fractures is not well documented. Design: Cross-sectional study. Methods: We studied 59 patients receiving L-thyroxine suppressive therapy for differentiated thyroid carcinoma (DTC). BMD of the hip was measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 41 publications
(20 reference statements)
2
50
0
Order By: Relevance
“…Several studies carried out in patients with iatrogenic hyperthyroidism showed that the risk for fracture was higher in older men and mainly in women with a very low TSH level (30,31,32). However, it is not totally clear that iatrogenic hyperthyroidism does affect bone in a totally similar way as hyperthyroidism due to toxic goiter or autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies carried out in patients with iatrogenic hyperthyroidism showed that the risk for fracture was higher in older men and mainly in women with a very low TSH level (30,31,32). However, it is not totally clear that iatrogenic hyperthyroidism does affect bone in a totally similar way as hyperthyroidism due to toxic goiter or autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…First, it is possible that a large part of the cancers we have detected would not have had deleterious effects if not removed by surgery, as longitudinal studies on this matter are missing. Secondly, and more importantly, L-T 4 treatment is not without risk, with the negative effects of TSH-suppressive treatment with L-T 4 on cardiovascular system in aged subjects (Biondi et al 2002, Fazio et al 2004) and development of osteoporosis in post-menopausal women (Williams 1997, Heijckmann et al 2005) being well documented. Longitudinal case-control studies and careful evaluation of the cost-effectiveness of L-T 4 treatment are required to address this question.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were published also in the past (Shomon, 1995). Some on the other hand has confirmed that long term suppressive therapy affects bone turnover and bone mineral density in pre and postmenopausal women with TC (Heijekmann et al, 2005). Decrese in BMD as a result of suppressive therapy in TC was confirmed but this effect was ameliorated by preventive substitution of calcium and calcitonin (Mikosch et al, 2006).…”
Section: Discussionmentioning
confidence: 97%